Phosphatidylserine on sperm head interact with Annexin A5 on oviduct luminal cilia to form a sperm reservoir in pigs - Lorraine Schmaltz; Elie Barakat; Renaud Fleurot; Rustem Uzbekov; Karine Reynaud; Ludivine Laffont; Guillaume Tsikis; Isabelle Mérour; Pascal Mermillod; Marie Saint-Dizier (European Journal of Cell Biology)
After insemination, a subpopulation of sperm reaches the oviducts and binds to isthmic epithelial cells to form a “sperm reservoir”. Our objective was to explore the role of annexin A5 (ANXA5), a protein that binds with high affinity to phosphatidylserine (PS), in the formation of the sperm reservoir in pigs.Phosphatidylserine was detected on the head of approximately 10 % of boar sperm at ejaculation. Porcine ANXA5 was immunodetected with a strong signal on luminal cilia in the isthmus and in derived isthmic epithelial spheroids (IES). Exogenous PS between 0.01 and 0.1 µg/mL and recombinant porcine ANXA5 (rpANXA5) above 0.1 µg/mL inhibited sperm binding to IES without reducing sperm motility. Pre-incubation of sperm, but not IES, with rpANXA5 inhibited sperm binding to IES. Under capacitating conditions, the proportion of live sperm with head PS exposure and the ability of sperm to bind to rpANXA5 and IES cilia increased within 30 min. Conversely, the acrosome reaction decreased the ability of sperm to bind rpANXA5 and prevented sperm binding to IES.In conclusion, sperm membrane remodelling during capacitation enhanced head PS exposure in motile sperm, resulting in increased interaction with ciliary ANXA5 on isthmic epithelial spheroids. These findings support a role for PS-ANXA5 interaction in the formation of the sperm reservoir in mammalian females.